A Study on Training and Development among the Employees in Tamilnadu State Transport Corporation (TNSTC) - Lawenya, S.; Santhana Raj, L. (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
This paper discusses about a study on Training and Development among the employees in Tamil Nadu State Transport Corporation (TNSTC). Training and Development is very important in every organization. Training and Development programs are essential for the employees to be well trained and educated for successfully reaching the attainment of the organizational goals. It is used to improve the effectiveness of training, skills, knowledge, abilities and work performance of the employees. Training and development programs can be very useful for the employees to tackle the situations and give solutions to the problems. Training and development can also be used to change the workforce attitudes, job performance, behaviour and creative thinking. There are two techniques of training and development; they are (1) On-the job training, (2) Off-the job training. Many challenges can be faced by employees to improve their job performance, relationship between the employers and the employees and to develop the organizational achievements.